Magnitude of Intestinal Parasitosis, Malnutrition, and Predictors of Anemia Among Nonpregnant Reproductive-Age Women Attending Healthcare Services in Olenchity General Hospital, Central Ethiopia - Yada, Tesema Abera; Dessie, Yadeta; Darghawth, Rasha; Wilfong, Tara; Kure, Mohammed Abdurke; Roba, Kedir Teji (Frontiers in Tropical Diseases, 2021)
Background Anemia and malnutrition remain a public health challenge in developing worlds. Anemia during a nonpregnant state is one of the neglected medical conditions affecting reproductive-age women around the world. Globally, it is estimated that one-third of all reproductive-age women are anemic. Although it has negative consequences and extensive burden, anemia in nonreproductive-age women is rarely studied in Africa. In Ethiopia, studies investigating anemia and malnutrition among nonpregnant reproductive-age women are limited. Therefore, this study was aimed to assess intestinal parasitic infection, malnutrition, and predictors of anemia among nonpregnant reproductive-age women in Olenchity General Hospital, central Ethiopia. Methods A facility-based cross-sectional study design was employed among 405 nonpregnant reproductive-age women in Olenchity General Hospital, central Ethiopia from February 14 to March 24, 2018. Data were collected using a pretested interviewer-administered questionnaire. Blood samples were collected and tested to determine hemoglobin levels by using a hematology analyzer machine. Collected data were entered into EpiData version 3.02 and exported to SPSS version 20 (IBM SPSS Statistics, 2012) for further analysis. Multivariable logistic regression analysis was done to identify factors independently associated with anemia after controlling for possible confounders. Statistical significance was declared at p-value <0.05. Result Overall, the magnitude of anemia was found to be 47.4% [95% CI (42.7, 52.6)], of which 34.8% were mild, 11.4% were moderate, and 1.2% were severely anemic. The prevalence of intestinal parasitic infection, wasting, and overweight was 34.6%, 26.2%, and 8.1%, respectively. Having no formal education [AOR=2.25, CI (1.02, 4.97)], using three to five sanitary pads per day during menses [AOR=1.66 CI (1.02, 2.68)], history of chewing khat [AOR= 4.45, CI (1.18, 16.83)], being from households with mild food insecurity [AOR=3.41, CI (1.10, 10.58)], and intestinal parasitic infection [AOR=2.28, CI (1.39, 3.47)] were factors independently associated with anemia. Conclusion The magnitude of anemia, malnutrition, and intestinal parasitic infection among nonpregnant reproductive-age women was found to be a considerable public health problem. Therefore, attention should be given to nonpregnant reproductive-age women visiting different healthcare services to reduce risks of anemia and malnutrition for possible future pregnancies and to ensure women’s health. Deworming of nonpregnant reproductive-age women is also very crucial to reduce the risks of anemia.